2015
DOI: 10.1371/journal.pone.0144781
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects and Mechanism of Novel Emodin Rhamnoside Derivatives against Human Cancer Cells In Vitro

Abstract: A series of novel anthracene L-rhamnopyranosides compounds were designed and synthesized and their anti-proliferative activities on cancer cell lines were investigated. We found that one derivative S-8 (EM-d-Rha) strongly inhibited cell proliferation of a panel of different human cancer cell lines including A549, HepG2, OVCAR-3, HeLa and K562 and SGC-790 cell lines, and displayed IC50 values in low micro-molar ranges, which are ten folds more effective than emodin. In addition, we found EM-d-Rha (3-(2”,3”-Di-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Emodin (D1) has been reported to inhibit the proliferation of many cancer cells which include; Colon cancer [3] [4], breast cancer [5] [6], gall bladder cancer [7] [8], pancreatic cancer [9], lung cancer [10] [11] and human cervical cancer [12]. Poor bioavailability and toxicity in vivo have been documented to limit emodin as cancer chemotherapy [13]. Natural emodin glycoside derivatives have been reported to possess high antitumor activities than emodin [13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Emodin (D1) has been reported to inhibit the proliferation of many cancer cells which include; Colon cancer [3] [4], breast cancer [5] [6], gall bladder cancer [7] [8], pancreatic cancer [9], lung cancer [10] [11] and human cervical cancer [12]. Poor bioavailability and toxicity in vivo have been documented to limit emodin as cancer chemotherapy [13]. Natural emodin glycoside derivatives have been reported to possess high antitumor activities than emodin [13].…”
Section: Introductionmentioning
confidence: 99%
“…Poor bioavailability and toxicity in vivo have been documented to limit emodin as cancer chemotherapy [13]. Natural emodin glycoside derivatives have been reported to possess high antitumor activities than emodin [13]. It has been shown that modification of the glycoside by addition of sugar chain at carbon-3 hydroxide (C3-OH) increases solubility and antitumor activity of emodin [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations